Identifying access barriers faced by rural and dispersed communities to better address their needs: implications and lessons learned for rural proofing for health in the Americas and beyond - Natalia Houghton; Ernesto Bascolo; Rachael Cohen; Norma Lleny Cruz Vilcarromero; Hernán Rodriguez Gonzalez; Daniel Albrecht; Theadora Koller; James Fitzgerald (James Cook University, 2023)
Introduction: Universal access to health services and universal health coverage are needed to achieve good health for all, yet rural communities face a variety of access barriers. As part of an effort to 'rural proof' health systems, it is therefore imperative to identify and act on the factors limiting access to health services by rural and indigenous communities. This article provides a comprehensive overview of the wide range of access barriers faced by rural and remote communities in two countries where barrier assessments were conducted. It also discusses the potential for barrier assessments to contribute evidence for rural proofing of national health policies, strategies, plans and programs. Methods: The study applied a concurrent triangulation design to collect and analyze data obtained from narrative-style literature reviews, in-depth interviews with local health authorities, and secondary analyses of existing household data on Guyana and Peru. These two countries were selected because they have some of the largest rural and indigenous populations in Latin America and the Caribbean, and have national policies in place for providing free, essential health services for these communities. Both quantitative and qualitative data were collected separately, and results were interpreted together. The main objective was to corroborate and cross-validate findings looking for convergence between the separate data analyses. Results: Seven dominant themes were identified across the two countries: use of traditional medicine and practice; decision making, gender, and family power dynamics; ethnicity and trust; knowledge and health literacy; geographic accessibility, health personnel and intercultural skills; and financial accessibility. The findings suggest that the interaction between these barriers may be as important as the singular role played by each factor, thereby highlighting the complex and multifactorial nature of accessing services in rural settings. Issues with limited availability of human resources for health were compounded by inadequate supplies and infrastructure. Financial barriers were often linked to the indirect costs of transport and geographic location, and further exacerbated by reduced socioeconomic status of rural communities, a majority of which are indigenous and have a strong preference for traditional medicines. Importantly, rural and indigenous communities experience considerable non-financial barriers related to issues of acceptability, which requires adaptation of health personnel and health service delivery models to the context-specific needs and realities of each rural community. Conclusion: This study presented an approach for data collection and analysis that is both feasible and effective for evaluating access barriers in rural and remote communities. While this study explored access barriers through general health services in two rural settings, the issues identified reflect the structural deficiencies of many health systems. These challenges and singularities require adaptive organizational models for the provision of health services that respond to the specific characteristics of rural and indigenous communities. This study indicates the potential relevance of conducting assessments of barriers to health services as part of a wider approach to rural proofing and supports the notion that a mixed-methods approach, linking secondary analysis of existing relevant national survey data with focused key-informant interview data, may be an effective and efficient way to transform data into the knowledge policymakers need to rural proof health policies.